Purification and properties of a new dehalogenase enzyme from Pseudomonas sp. B6P grow in 3- chloropropionate (3CP) - Tengku Abdul Hamid, Tengku Haziyamin; Hamid, A. A. A; Zulkifly, Nurul Asma Hasliza; Hamdan, Sallehuddin; Ariffin, Shahrul Hisham Zainal; Huyop, Fahrul Zaman (Academic Journals, 2011)
Halogenated compounds are widely used in agriculture and industries and have been associated with environmental pollution. Degradation of 3-chloropropionate (3CP) by microorganism has been established and this enzyme could only remove halogen atom at the - position of 3-carbon alkanoic acids. Pseudomonas sp. B6P was originally isolated from paddy field which was able to degrade 3CP therefore, suggesting it may have some desirable properties. The enzyme was purified from cell-free extracts having a monomer of 56,000 Da. It was found to be stable between pH 5 to 8 and its optimal pH was 8. Its activity was not affected by metal ions such as Mn2+, Fe3+ and Mg2+, but was inhibited by Hg2+ and Ag2+. The enzyme is specific for 3CP, and the Km value (0.20 mM ± 0.05).